Improving maternal mental health through digital-based social support - Evi Kurniasari Purwaningrum; Yoga Achmad Ramadhan; Siti Khotimah; Yunia Sherlyna; Erdin Jhaya Saputra; Shinta Rahmadina Agustin; Nuryan Ayu (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang)
Pregnant women are vulnerable to various mental health issues, such as anxiety, depression, and excessive stress. These conditions are often exacerbated by a lack of social support and negative stigma, which discourage pregnant women from seeking help. If left unaddressed, mental health problems can negatively impact both maternal and fetal health, including increased risks of pregnancy complications and developmental disorders in the fetus. To address these challenges, a digital-based program was developed to provide social support and enhance the mental health of pregnant women. This community service initiative also included mental health education and relaxation training to help maintain psychological well-being among pregnant women. The evaluation results showed significant improvements across all assessed aspects. The total score increased from 5.5 in the pretest to 8.0 in the posttest. Knowledge of mental health increased from 5.5 to 8.0, strategies for maintaining mental health improved from 5.2 to 8.2, and understanding how to seek help rose from 5.3 to 8.1. Additionally, knowledge of relaxation techniques increased from 5.1 to 8.3, while the ability to apply these techniques independently improved from 4.9 to 8.0. These findings demonstrate that the digital-based program is effective in helping pregnant women address mental health challenges and improve their psychological well-being.